Intention to Engage in Winter Sport in Climate Change Affected Environments - Frühauf, Anika; Niedermeier, Martin; Kopp, Martin (Frontiers in Public Health, 2020)
Exercise, including winter sport activities, shows positive effects on physical and mental health, with additional benefits when participating in natural environments. Winter sport activities are particularly vulnerable to climate change, since global warming will decrease the duration and amount of snow. In the context of climate change in Alpine environments, little is known on the determinants of winter sport behavior. Thus, the following study primarily aimed at comparing the effect of being exposed to pictures of a climate change affected scenario (CCA) to an unaffected scenario (CCU) on the intention to engage in recreational winter sport activities. Secondly, we aimed to analyze the role of anticipated affective responses during exercising based on the Theory of Planned Behavior (TPB). An experimental cross-sectional web-based study design was used. Participants were randomly allocated to pictures of either CCA or CCU. TPB variables and affective responses with regard to the displayed scenarios were assessed. Statistical analyses included Mann-Whitney-U Tests, linear regression and mediation analyses. Significant group differences were seen in all TPB variables, p<.038; -.13